EFEKTIVITAS TEH HERBAL BIT TERHADAP STATUS HEMATOLOGI REMAJA PUTRI ANEMIA - Novita Sari Br Pelawi; Sri Rahayu; Sri Endang Windiarti (LPPM Universitas Abdurrab, 2026)
Anemia among adolescent girls remains a significant public health problem in Indonesia and is largely caused by iron deficiency, low adherence to iron supplementation, and the habitual consumption of beverages that inhibit iron absorption. This study aimed to analyze the effect of beetroot herbal tea as a complementary therapy on hemoglobin levels, hematocrit, and erythrocyte count in anemic adolescent girls. This quantitative study employed a true experimental design with a randomized pre-test and post-test control group. The sample consisted of 40 adolescent girls aged 16–19 years with mild to moderate anemia, who were randomly assigned to an intervention group (n=20) receiving 2 g/day of beetroot herbal tea brewed in 250 mL of warm water and 60 mg of iron supplementation once daily for 14 days, and a control group (n=20) receiving only 60 mg of iron supplementation once daily for 14 days. Hemoglobin, hematocrit, and erythrocyte levels were measured before and after the intervention using a hematology analyzer. Data were analyzed using the Wilcoxon and Mann–Whitney tests following the Shapiro–Wilk normality test. The results showed that the combination of beetroot herbal tea and iron supplementation significantly increased hemoglobin levels, hematocrit, and erythrocyte counts compared to the control group (p<0.05) with large effect sizes across all hematological parameters. It can be concluded that beetroot herbal tea is an effective, safe, and promising complementary therapy for improving hematological status in anemic adolescent girls. Beetroot herbal tea is recommended to be developed as a complementary intervention in anemia prevention and control programs for adolescent girls, particularly as an adjunct to iron supplementation in school-based settings. Further studies with longer intervention periods and comprehensive iron status biomarkers are recommended to strengthen the evidence and support its implementation in public health practice